2014
DOI: 10.1016/j.hlc.2014.04.131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Deep Hypothermic Circulatory Arrest on the Blood Brain Barrier in a Cardiopulmonary Bypass Model – A Pilot Study

Abstract: Background Neurologic injury is common after cardiac surgery and disruption of the blood brain barrier (BBB) has been proposed as a contributing factor. We sought to study BBB characteristics in a rodent model of cardiopulmonary bypass (CPB) and deep hypothermic circulatory arrest (DHCA). Methods Adult rats were subjected to CPB/DHCA or to sham surgery. Analysis included Western blotting of relevant BBB proteins in addition to in vivo brain magnetic resonance imaging (MRI) using a clinically used low-molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…In normal physiology, tight junctions between endothelial cells maintain the integrity of the blood-CSF barrier. However, the blood-brain barrier (BBB) is disrupted after HCA [7, 12, 29, 30], which creates an opportunity for nanoparticles to enter the brain parenchyma. Although the precise size of blood-CSF barrier leakage in the HCA-induced brain injury is unclear in this model, our results suggest that crossing of the BBB is facilitated by the hydroxyl-terminated PAMAM dendrimers’ sub-10 nm size and neutrally-charged surface properties.…”
Section: Resultsmentioning
confidence: 99%
“…In normal physiology, tight junctions between endothelial cells maintain the integrity of the blood-CSF barrier. However, the blood-brain barrier (BBB) is disrupted after HCA [7, 12, 29, 30], which creates an opportunity for nanoparticles to enter the brain parenchyma. Although the precise size of blood-CSF barrier leakage in the HCA-induced brain injury is unclear in this model, our results suggest that crossing of the BBB is facilitated by the hydroxyl-terminated PAMAM dendrimers’ sub-10 nm size and neutrally-charged surface properties.…”
Section: Resultsmentioning
confidence: 99%
“…Animal studies have suggested the POCD may be caused be either excessive neuroinflammation after surgery (79), a failure to resolve inflammation (80,81), blood-brain barrier/endothelial dysfunction (8284), and/or pre-existing Alzheimer’s disease pathology (reviewed in (28)). Activation of the innate immune system is increasingly appreciated as an underlying factor in several neurodegenerative conditions, including Alzheimer’s disease.…”
Section: What Causes Pocd?mentioning
confidence: 99%
“…Similar neuropathology with macrophage infiltration and defective phagocytosis has been highlighted in the brain of AD patients (66) and this may be mediated by changes in BBB permeability during the neurodegenerative process (67). Changes in BBB permeability and function have been reported in several models of surgery-induced cognitive decline, including orthopedic (30), cardiac (68) and abdominal (54) surgery-induced cognitive decline, suggesting a role of endothelial and other glia cells contributing to cognitive decline.…”
Section: Neuroinflammation and Cns Functionmentioning
confidence: 56%